Imidazole-containing Co2+ and Ni2+ etidronates: crystal structures and electrochemical behaviour - Bazaga-García, Montse; Pérez-Colodrero, Rosario Mercedes; Vílchez-Cózar, Álvaro; Armakola, Eirini; Gjika, M.; Visa, Aurelia; Choquesillo-Lazarte, Duane; Olivera-Pastor, Pascual; Cabeza-Díaz, Aurelio; Demadis, Konstantinos D. (My University, 2021)
Metal phosphonates-based coordination polymers (CPs) are known to exhibit versatile structural diversity and functionality. Thus, they have been used, among other applications, as electrocatalyst precursors for both, PEMFCs and electrolysers. In this work, we report the synthesis, crystal structure and electrochemical properties of imidazole-containing Co2+, Ni2+ and Zn2+ derivatives of the etidronic acid, (HO)2P(O)-C(CH3)(OH)-P(O)(OH)2 (ETID). Analyses of the crystal structures reveals that these solids are 1D, in which the imidazole molecules form part of the coordination sphere of the cations (Co2+, Ni2+) or act as charge-compensating imidazolium cations (Zn2+). Co2+ and Ni2+ solids were pyrolysed under 5% H2/Ar atmosphere at different temperatures. The resulting metal phosphides were tested as electrocatalysts for the Oxygen Evolution and Reduction Reactions (OER and ORR, respectively) and the Hydrogen Evolution Reaction (HER). Preliminary results indicate that Co2+ derivatives exhibit better performance.
Proyecto Nacional PID2019-110249RB-I00, PAIDI2020 de la Junta de Andalucia, Ayudas del Plan Propio de Investigación de la Universidad de Málaga para la contratación predoctoral (PRE2020-094459).
Keywords: Química organometálica; Coordination polymers; OER; ORR; HER; Phosphonates; Imidazole; Electrocatalyst